Quantitative MRI T2 relaxometry of knee joint in early detection of osteoarthritis (Journal of Fatima Jinnah Medical University, 2022)
Background: Magnetic resonance imaging (MRI) T2 is an advance modality for the early diagnosis of osteoarthritis. This study was performed to determine the MRI T2 relaxometry value of knee joint in early detection of osteoarthritis among suspected cases.Patients and methods: This observational study was conducted at Department of Radiology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan from 20th September 2020 to 28th February 2021. All patients aged 20-60 years of either gender suspected of knee osteoarthritis were consecutively enrolled. Osteoarthritis was confirmed based on Kellgren & Lawrence (KL) radiographic grading of 2-5. MRI T2 relaxometry was performed in all patients.Results: Of 102 patients, there were 67 (65.7%) males and 35 (34.3%) females. Mean age was 43.72 ±14.01 years. KL grading showed that KL grade 0 observed in 29 (28.4%), grade I in 13 (12.7%), grade II in 25 (24.5%), grade III in 30 (29.4%), and grade IV in 5 (4.9%) patients. The frequency of osteoarthritis was found in 60 (58.8%) patients. Mean MRI T2 value was found to be 94.12 ±16.32. Mean MRI T2 value was found significantly higher in patients with KL grade IV (109.89 ±5.38) followed by KL grade III (107.35 ±3.24), KL grade II (97.72 ±14.65), KL grade I (89.54 ±13.69), and KL grade 0 (76.65 ±10.56). (p-value
Keywords: Quantitative T2 Relaxometry; Magnetic Resonance Imaging; Knee Joint; Osteoarthritis